Organization and support as an essential part of group exercise programs for older people with dementia: an end-user interview study - Taraldsen, Kristin; Nygård, Arnhild J.; Boulton, Elisabeth; Grønningsæter, Guro; Erland, Marit H.; Waldenstrøm, Nina; Johnsen, Linda; Tangen, Gro G.; Granbo, Randi (Frontiers in Sports and Active Living, 2025)
IntroductionDevelopment of accessible group exercise sessions is warranted for home-dwelling older people with cognitive impairment or dementia. This study aims to explore the experiences of participants in a group exercise session organized with volunteers both as instructors and as those providing support for the participants.MethodsThis qualitative descriptive study reports on a primary analysis of qualitative data collected through semistructured focus group interviews with 12 people with cognitive impairment or dementia at three group exercise sessions in three municipalities. Interviews were audio-recorded, transcribed, and analyzed using thematic analysis.ResultsParticipants expressed an overall satisfaction with the new group exercise sessions. We found four meaning units forming a chain of support. The participants highlighted support to be motivated enough to engage in the sessions, support by offering transportation, the exercise content, and the role of instructors. Overall, the participants expressed that these exercise sessions had become a social arena for them, and all wanted to continue.Discussion and conclusionsExercise groups can be a meaningful and social arena for people with cognitive impairment or dementia, through careful organization with volunteers and minimal involvement from informal caregivers. This study underlines the need for properly organized activities, outside the home, to overcome the challenges associated with participation for this population.